Formation of Diamond-Like Carbon Coatings by Chemical Deposition in High Density Plasma - N. V. Leonovich; P. D. Tovt; D. A. Kotov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
A developed technological reactor for the formation of a diamond-like carbon coating on substrates up to 200 mm in diameter by chemical vapor deposition in high-density inductively coupled plasma at an operating pressure below 5 Pa is described. The results of experimental studies on obtaining a diamond-like carbon coating in the developed reactor are presented. The dependences of the rate of deposition of a diamond-like carbon coating on the power of the RF discharge, the operating pressure, and the consumption of the film-forming gaseous reagent have been established. Also, for the developed technological reactor, the modes for obtaining diamond-like carbon coatings with the best mechanical properties were established with the following process parameters: RF power 600–900 W, precursor gas flow rate 15–50 cm3/min, the ratio of plasma-forming gas volumes to film-forming gas volume 3:1 at a residual pressure in the working chamber of not more than 4 Pa. It has been shown by Raman spectroscopy that the coatings obtained under efficient conditions contain a significant amount of a diamond-like phase.